2014
DOI: 10.1021/ez500055f
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Organic Aerosol Formation via 2-Methyl-3-buten-2-ol Photooxidation: Evidence of Acid-Catalyzed Reactive Uptake of Epoxides

Abstract: Secondary organic aerosol (SOA) formation from 2-methyl-3-buten-2-ol (MBO) photooxidation has recently been observed in both field and laboratory studies. Similar to the level of isoprene, the level of MBO-derived SOA increases with elevated aerosol acidity in the absence of nitric oxide; therefore, an epoxide intermediate, (3,3-dimethyloxiran-2-yl)methanol (MBO epoxide), was synthesized and tentatively proposed to explain this enhancement. In this study, the potential of the synthetic MBO epoxide to form SOA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 28 publications
3
49
0
Order By: Relevance
“…A previous study by Dommen et al (2006) on the effect of RH under high NO x conditions indicated that more volatile SOA were observed at higher RH rather than at lower RH. Additionally, SOA formation, including carboxylic acids and organosulfur compounds in cloud and fog droplets, have been hypothesized as plausible by Blando and Turpin (2000), while a recent smog chamber study by Zhang et al (2012a) suggested that elevated RH values could mediate the formation of organosulfates, thereby emphasizing the role of wet sulfate aerosols in forming organosulfates in ambient aerosols. At the same time, though aerosol acidity has been found to enhance isoprene SOA formation under low initial NO conditions (Surratt et al, 2007c(Surratt et al, , 2010Jaoui et al, 2010), seed aerosol acidity showed a negligible effect on SOA formation from isoprene under high initial NO conditions , which implied the less important role of seed aerosol acidity on the formation of OS 210 on 7 and 8 June (daytime) where both NO and RH were high.…”
Section: Local Impactsmentioning
confidence: 98%
“…A previous study by Dommen et al (2006) on the effect of RH under high NO x conditions indicated that more volatile SOA were observed at higher RH rather than at lower RH. Additionally, SOA formation, including carboxylic acids and organosulfur compounds in cloud and fog droplets, have been hypothesized as plausible by Blando and Turpin (2000), while a recent smog chamber study by Zhang et al (2012a) suggested that elevated RH values could mediate the formation of organosulfates, thereby emphasizing the role of wet sulfate aerosols in forming organosulfates in ambient aerosols. At the same time, though aerosol acidity has been found to enhance isoprene SOA formation under low initial NO conditions (Surratt et al, 2007c(Surratt et al, , 2010Jaoui et al, 2010), seed aerosol acidity showed a negligible effect on SOA formation from isoprene under high initial NO conditions , which implied the less important role of seed aerosol acidity on the formation of OS 210 on 7 and 8 June (daytime) where both NO and RH were high.…”
Section: Local Impactsmentioning
confidence: 98%
“…While the nitrate nucleophile was not directly studied in these experiments, because its relative nucleophilicity has been found to be similar to sulfate for reactions with isoprene-derived epoxides , it is expected for MAE reactions that sulfate and nitrate would have similarly nucleophilicities. While hetero-oligomers, formed from cross reactions of MAE with other atmospherically relevant epoxides (such as IEPOX and 2-methyl-3-buten-2-ol-derived (Zhang et al, 2014) epoxides), might be formed on ambient SOA, these epoxides are also expected to have mediocre nucleophilic strength (they are probably more similar to 2-MG than to methanol), and these reactions would also probably not be competitive with reactions involving more abundant nucleophiles. Thus far, field studies have identified only two likely MAE reaction products, 2-MG and the diester , which are likely formed from hydrolysis of MAE and the reaction of MAE with 2-MG, respectively.…”
Section: Mae Nucleophilic Reactions On Soamentioning
confidence: 99%
“…The authors further found that organonitrates could easily be transformed to organosulfates during hydrolysis in the presence of sulfate. Some studies also showed that 2-methyl-3-buten-2-ol (MBO), due to its emissions that are larger than isoprene in some regions (Baker et al, 1999), is an important precursor for organosulfates and SOA in the atmosphere through its reactions with OH under NO and aerosol acidity conditions and from acid-catalysed reactive uptake of MBO-based epoxides formed during MBO photooxidation (Mael et al, 2015;Zhang et al, 2012Zhang et al, , 2014. Organosulfate formation was also found from oxidation of hydroxyhydroperoxides (Riva et al, 2016) and from heterogeneous reactions of SO 2 with selected long-chain alkenes and unsaturated fatty acids (Passananti et al, 2016).…”
Section: Introductionmentioning
confidence: 99%